Approaches to measuring use of research evidence in K-12 settings: A systematic review. (June 2019) - Lawlor, Jennifer; Mills, Kristen; Neal, Zachary; Neal, Jennifer Watling; Wilson, Camren; McAlindon, Kathryn
Abstract: An increased focus on the use of research evidence (URE) in K-12 education has led to a proliferation of instruments measuring URE in K-12 education settings. However, to date, there has been no review of these measures to inform education researchers' assessment of URE. Here, we systematically review published quantitative measurement instruments in K-12 education. Findings suggest that instruments broadly assess user characteristics, environmental characteristics, and implementation and practices. In reviewing instrument quality, we found that studies infrequently report reliability, validity, and demographics about the instruments they develop or use. Future work evaluating and developing instruments should explore environmental characteristics that affect URE, generate items that match up with URE theory, and follow standards for establishing instrument reliability and validity. Highlights: Many instruments exist to measure use of research evidence in K-12 school settings. Details about these instruments' reliability and validity is sparse. The SN-EBP, QURBI, and SPUR instruments offer promising options.